ANALISIS NILAI TUKAR NELAYAN (NTN) NELAYAN PUKAT CINCIN DI KAMPUNG TALISAYAN KECAMATAN TALISAYAN KABUPATEN BERAU - Andi Rahman; Erwiantono (Jurnal Pembangunan Perikanan dan Agribisnis, 2021)
Talisayan is one of the southern coastal areas, which is located in Talisayan District, Berau Regency, East Kalimantan. Talisayan village has abundant natural resources especially in the fisheries sector so that most Talisayan citizens work as fishermen to escalate their families' prosperity. The purpose of this study was to determine the prosperity level of fishermen in Talisayan Village Talisayan District by using Fishermen Exchange Rate (NTN) analysis and saving habits of fishermen society in Talisayan Village. This research was conducted in February 2019 - January 2020 in Talisayan Village, Talisayan District, Berau Regency. A case study research method was used in this research, a detailed research on an object of research. The purposive sampling method was used with a total 4 respondents. The data were analyzed using descriptive qualitative-quantitative methods with a focus on Fishermen's Exchange Rate (NTN) analysis method, Fishermen's Exchange Rate Index (INTN) and a description to describe the fishermen saving habits. The result of the NTN analysis shows that in general NTN values ​​of fishermen families of six types of fishing gear in 2018 and 2019 was with an average above one. The result of INTN analysis of fishermen families in 2018 and 2019 was with an average above 100%. Keywords : Fishermen Exchange Rate (NTN), Saving Habits, Fishermen, Talisayan Village